2014
DOI: 10.4172/2167-7948.1000183
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer: Molecular Characteristics of Radiation-Associated Papillary Thyroid Cancer, with a Special Reference to of Atomic Radiation Exposure

Abstract: Among atomic-bomb (A-bomb) survivors of Hiroshima and , incidence of thyroid cancer significantly increased after exposure to nuclear radiation. This review will focus on the initiating gene alterations in the development of adult-onset papillary thyroid cancer (PTC) among A-bomb survivors. The effects of A-bomb radiation on chromosomal rearrangements (RET and NTRK1 rearrangements) and point mutations (BRAF and RAS mutations) after exposure were different. In contrast to PTC cases with point mutations, PTC cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Recently, a new paracentric inversion of chromosome 7q leads to an inframe fusion between exons 1-8 of the AKAP9 gene and exons 9-18 of BRAF. The fusion protein transforms NIH3T3 cells, confirming its oncogenic properties 32,33 . Iodine induced goiter, hyperthyroidism(IIT)and thyrotoxicosis(IIT) , who reported that goitrous individuals treated with iodine developed hyperthyroidism.…”
mentioning
confidence: 69%
“…Recently, a new paracentric inversion of chromosome 7q leads to an inframe fusion between exons 1-8 of the AKAP9 gene and exons 9-18 of BRAF. The fusion protein transforms NIH3T3 cells, confirming its oncogenic properties 32,33 . Iodine induced goiter, hyperthyroidism(IIT)and thyrotoxicosis(IIT) , who reported that goitrous individuals treated with iodine developed hyperthyroidism.…”
mentioning
confidence: 69%